Colon Polypectomy Current Techniques and Novel Perspectives (Springer International Publishing, 2018)
This book provides a comprehensive and up-to-date overview of current polypectomy techniques and describes new perspectives in the field. A wide variety of topics are covered, including classification of colon polyps, established polypectomy techniques and related controversies, advanced endoscopic resection, endoscopic submucosal dissection, the use of submucosal injection solutions, management of complications, management of anticoagulant and antiplatelet medications, and post-polypectomy endoscopic surveillance. Information is also provided on a novel risk calculation score for adenoma recurrence after polypectomy, developed by the editors of the book and their colleagues. In acquainting readers with the state of the art in the field, Colon Polypectomy will serve as a valuable reference and practical tool for all who perform the procedure, which is of ever-increasing importance given the recent success of colon cancer screening campaigns in leading to earlier detection of colon polyps.